Shelley Duvall's Faerie tale theatre. Bedtime tales [videorecording (DVD)] - Duvall, Shelley, 1949-; Christopher, Dennis; Gould, Elliott; D'Angelo, Beverly; Peters, Bernadette; Reeve, Christopher, 1952-2004; Stanton, Harry Dean, 1926-2017; O'Neal, Tatum, 1963-; Karras, Alex (Faerie tale theatre., 2009)
"Talking bears, sleeping giants, handsome princes, evil fairies and more fill this 4-episode collection from the award-winning series. Some of the most treasured bedtime stories are brought to life with glorious productions and magnificent costumes that will leave you dreaming... happily ever after."--container.